KH2PO4 Production by Cooling Crystallization Using Its Phase Equilibrium in the KH2PO4‐KCl‐C2H5OH‐H2O System. Issue 7 (9th June 2017) - Ren, Yongsheng; Liu, Jiamin; Ma, Jingjing; Cai, Chao
Abstract: Solid‐liquid phase equilibrium and physicochemical properties of the KCl‐KH2 PO4 ‐C2 H5 OH‐H2 O system at 313.15 K were investigated by the method of isothermal solution saturation, and the equilibrium solids were analyzed by Schreinemaker's method of wet residues and verified by XRD. Drowning‐out precipitation of KH2 PO4 was carried out by mixing different ethanolic aqueous solutions, and crystal morphology was observed by polarizing microscopy. The phase diagrams exhibit one eutonic point, two univariant curves, and crystallization regions corresponding to KCl and KH2 PO4 . At all studied ethanol concentrations, the crystallization region of KH2 PO4 is larger than that of KCl. The effect of KCl (ethanol) on crystal growth morphology and KH2 PO4 product quality was studied. Abstract : The KCl‐KH2 PO4 ‐C2 H5 OH‐H2 O system is relevant to process design for the crystallization of KH2 PO4 . Hence, its solid‐liquid phase equilibrium, solubility data, and physicochemical properties were determined at 313.15 K. Drowning‐out precipitation of KH2 PO4 was carried out in order to observe the crystal morphology, and the effect of KCl on KH2 PO4 crystallization was investigated.